Epigenetic regulation of normal human mammary cell type–specific miRNAs - Vrba, Lukas; Garbe, James C.; Stampfer, Martha R.; Futscher, Bernard W. (Genome Research, 2011)
Epigenetic mechanisms are important regulators of cell type–specific genes, including miRNAs. In order to identify cell type–specific miRNAs regulated by epigenetic mechanisms, we undertook a global analysis of miRNA expression and epigenetic states in three isogenic pairs of human mammary epithelial cells (HMEC) and human mammary fibroblasts (HMF), which represent two differentiated cell types typically present within a given organ, each with a distinct phenotype and a distinct epigenotype. While miRNA expression and epigenetic states showed strong interindividual concordance within a given cell type, almost 10% of the expressed miRNA showed a cell type–specific pattern of expression that was linked to the epigenetic state of their promoter. The tissue-specific miRNA genes were epigenetically repressed in nonexpressing cells by DNA methylation (38%) and H3K27me3 (58%), with only a small set of miRNAs (21%) showing a dual epigenetic repression where both DNA methylation and H3K27me3 were present at their promoters, such as MIR10A and MIR10B. Individual miRNA clusters of closely related miRNA gene families can each display cell type–specific repression by the same or complementary epigenetic mechanisms, such as the MIR200 family, and MIR205, where fibroblasts repress MIR200C/141 by DNA methylation, MIR200A/200B/429 by H3K27me3, and MIR205 by both DNA methylation and H3K27me3. Since deregulation of many of the epigenetically regulated miRNAs that we identified have been linked to disease processes such as cancer, it is predicted that compromise of the epigenetic control mechanisms is important for this process. Overall, these results highlight the importance of epigenetic regulation in the control of normal cell type–specific miRNA expression.